Book Review: Policy Integration for Complex Environmental Problems: the Example of Mediterranean Desertification by Helen Briassoulis (Editor). (10th March 2009) - Huge, Jean
Policy Integration for Complex Environmental Problems: the Example of Mediterranean Desertification, [edited] by Helen Briassoulis. Aldershot, Ashgate, 2005. 371 pp. ISBN 0-7546-2324-7